Progress in the Application of Artificial Intelligence in Mental Health Education for College Students in Universities - Shuai, Peng; Liu, Yue (IC-ITECHS, 2024)
The purpose of this paper is to explore how artificial intelligence technology can help mental health education in colleges and universities, analyse the progress of its application in personalised education, mental health monitoring and evaluation, ecological transient intervention, etc., and analyse its current situation, strengths, challenges, and future development direction.